“A privileged field of study”: Marcel Mauss and structural anthropology in Leiden - Oosten, Jarich (Études/Inuit/Studies, 2006)
AbstractStructural anthropology in Leiden was very much inspired by Mauss and the Année sociologique group. This paper focuses on the development of the “field of anthropological study” (FAS) that played an important role in the history of the structuralist movement in Leiden. Its definition was derived from the famous essay Seasonal Variations of the Eskimo by Mauss. J.P.B. de Josselin de Jong and P.E. de Josselin de Jong developed it into a conceptual tool for the comparative study of the Indonesian archipelago. In the early 1980s, the method was applied to the anthropological study of South Africa and to the comparative study of Indo-European mythology. Since 1986, it was also applied to solve core issues in the comparative study of Inuit culture. The FAS approach does not look primarily for similarities and generalisation, but for homologies, variations and transformations. In this respect, it corresponds to the valorisation of cultural differences by Inuit themselves. More than 100 years after it was developed by Mauss to explain the morphology of Inuit societies, the field of anthropological study still proves to be as rich and rewarding as ever.